Impact of the Nature of the Organic Spacer on the Crystallization Kinetics of UiO‐66(Zr)‐Type MOFs. Issue 19 (18th March 2015) - Ragon, Florence; Chevreau, Hubert; Devic, Thomas; Serre, Christian; Horcajada, Patricia
Abstract: The influence of the constitutive dicarboxylate linkers (size, functional group) over the crystallization kinetics of a series of porous Zr metal–organic frameworks with the UiO‐66 topology has been investigated by in situ time‐resolved energy dispersive X‐ray diffraction (EDXRD). Both large aromatic spacers (2, 6‐naphthalene‐, 4, 4′‐biphenyl‐ and 3, 3′‐dichloro‐4, 4′‐azobenzene‐dicarboxylates) and a series of X‐functionalized terephthalates (X=NH2, NO2, Br, CH3 ) were investigated in dimethylformamide (DMF) at different temperatures and compared with the parent UiO‐66. Using different crystallization models, rate constants and further kinetic parameters (such as activation energy) have been extracted. Finally, the impact of the replacement of the toxic DMF by water on the crystallization kinetics was studied through the synthesis of the functionalized UiO‐66‐NO2 solid. Abstract : Watch this spacer : The influence of the constitutive dicarboxylate linkers (size, functional group) over the crystallization kinetics of a series of porous UiO‐66‐type metal–organic frameworks (see figure) has been investigated by in situ time‐resolved energy dispersive X‐ray diffraction. The impact of the solvent (dimethylformamide vs. water) on the crystallization kinetics of UiO‐66‐NO2 was evaluated.